2021
DOI: 10.1021/acs.jpca.1c03061
|View full text |Cite
|
Sign up to set email alerts
|

CH Mode Mixing Determines the Band Shape of the Carboxylate Symmetric Stretch in Apo-EDTA, Ca2+–EDTA, and Mg2+–EDTA

Abstract: The infrared spectra of EDTA complexed with Ca 2+ and Mg 2+ contain, to date, unidentified vibrational bands. This study assigns the peaks in the linear and two-dimensional infrared spectra of EDTA, with and without either Ca 2+ or Mg 2+ ions. Two-dimensional infrared spectroscopy and DFT calculations reveal that, in both the presence and absence of ions, the carboxylate symmetric stretch and the terminal CH bending vibrations mix. We introduce a method to calculate participation coefficients that quantify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Such structural change affects the vibrational relaxation in two main ways. (1) As discussed in previous work on EDTA complexes, 30,31 the IVR process to lower energy modes becomes slower. (2) In addition, the conformation change associated with metal bound DTPA leads to an increase in the inter-site coupling as the carboxylate groups approach each other.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Such structural change affects the vibrational relaxation in two main ways. (1) As discussed in previous work on EDTA complexes, 30,31 the IVR process to lower energy modes becomes slower. (2) In addition, the conformation change associated with metal bound DTPA leads to an increase in the inter-site coupling as the carboxylate groups approach each other.…”
Section: Resultsmentioning
confidence: 89%
“…Previous work has demonstrated that the high frequency vibrational modes of carboxylate groups can be used to probe conformational and structural changes in the condensed phase. [28][29][30][31][32][33][34][35] In the context of previous PAC ligands, the ultrafast vibrational dynamics of EDTA's carboxylate groups have been extensively studied by the Baiz group 31 and the Garret-Roe group. 30 Using mid-IR pump-probe spectroscopy, the Baiz group measured the vibrational lifetime of the carboxylate groups in free and metal bound EDTA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the vibrational modes of the BTC ligands may serve as sensitive probes of the coordination and bonding environments. Changes in the carboxylate vibrational frequencies, for instance, can indicate subsequent increases/decreases in the charge transfer between the BTC ligand and the Am 3+ metal center …”
Section: Resultsmentioning
confidence: 99%
“…In the case of the antisymmetric stretching mode, these peaks are typically in a region with low spectral congestion, making them easier to identify than many other features in the fingerprint region of the spectrum. The positions of the carboxylate stretching signatures are sensitive to subtle changes in complex structure and charge distribution, making them both challenging to interpret and desirable to model. Here, we present a simple and generalizable relationship between the frequencies of the O–C–O stretching modes and the O–C–O bond angle (θ OCO ).…”
Section: Introductionmentioning
confidence: 99%